Neuronal regulated ire-1-dependent mRNA decay controls germline differentiation in Caenorhabditis elegans - Mor Levi-Ferber (eLife Sciences Publications Ltd, 2021)
Understanding the molecular events that regulate cell pluripotency versus acquisition of differentiated somatic cell fate is fundamentally important. Studies in Caenorhabditis elegans demonstrate that knockout of the germline-specific translation repressor gld-1 causes germ cells within tumorous gonads to form germline-derived teratoma. Previously we demonstrated that endoplasmic reticulum (ER) stress enhances this phenotype to suppress germline tumor progression(Levi-Ferber et al., 2015). Here, we identify a neuronal circuit that non-autonomously suppresses germline differentiation and show that it communicates with the gonad via the neurotransmitter serotonin to limit somatic differentiation of the tumorous germline. ER stress controls this circuit through regulated inositol requiring enzyme-1 (IRE-1)-dependent mRNA decay of transcripts encoding the neuropeptide FLP-6. Depletion of FLP-6 disrupts the circuit’s integrity and hence its ability to prevent somatic-fate acquisition by germline tumor cells. Our findings reveal mechanistically how ER stress enhances ectopic germline differentiation and demonstrate that regulated Ire1-dependent decay can affect animal physiology by controlling a specific neuronal circuit.